Kárpátalja logisztikai viszonyai - Bajor, Tibor (Közép-Európai Közlemények, 2016)
Transcarpathia in the Soviet Union and later became independent in Ukraine in many ways (economy, culture, transport) is positioned so of about the island. If we look at the transport is in the Carpathian mountains separates the area from the rest of Ukraine. Towards the interior of the country is practically two main roads lead and both operating, areas in the north-eastern side of the Carpathian Mountains central cities and counties have – Lviv and Ivano-Frankovsk – passing through. It is therefore extremely important for of transport logistics issues.This study overview and analysis of Transcarpathia logistical conditions. I present the formation of rail transport and characteristics, and the main features of each shipping and road transport.Study the final section summarizing the experiences inquiry; it will also make recommendations for change.